Combination therapy with a Tmprss6 RNAi‐therapeutic and the oral iron chelator deferiprone additively diminishes secondary iron overload in a mouse model of β‐thalassemia intermedia. Issue 4 (April 2015) - Schmidt, Paul J.; Racie, Tim; Westerman, Mark; Fitzgerald, Kevin; Butler, James S.; Fleming, Mark D.
Abstract : β‐thalassemias result from diminished β‐globin synthesis and are associated with ineffective erythropoiesis and secondary iron overload caused by inappropriately low levels of the iron regulatory hormone hepcidin. The serine protease TMPRSS6 attenuates hepcidin production in response to iron stores. Hepcidin induction reduces iron overload and mitigates anemia in murine models of β‐thalassemia intermedia. To further interrogate the efficacy of an RNAi‐therapeutic downregulating Tmprss6, β‐thalassemic Hbb th3/+ animals on an iron replete, an iron deficient, or an iron replete diet also containing the iron chelator deferiprone were treated with Tmprss6 siRNA. We demonstrate that the total body iron burden is markedly improved in Hbb th3/+ animals treated with siRNA and chelated with oral deferiprone, representing a significant improvement compared to either compound alone. These data indicate that siRNA suppression of Tmprss6, in conjunction with oral iron chelation therapy, may prove superior for treatment of anemia and secondary iron loading seen in β‐thalassemia intermedia. Am. J. Hematol. 90:310–313, 2015. © 2015 The Authors. American Journal of Hematology Published by Wiley Periodicals, Inc.